1976
DOI: 10.2214/ajr.126.1.107
|View full text |Cite
|
Sign up to set email alerts
|

External and interstitial radiation therapy of carcinoma of the oral tongue. A review of 32 years' experience

Abstract: ABSTRACT:In 204

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1978
1978
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…If LDR brachytherapy is used as a single modality in treating cancer of the oral cavity, the recommended dose is 65-70 Gy prescribed at a reference dose rate between 30-50 cGy/h [23,271, with as a consequence an overall treatment time limited to about 1 week, For such schedules an increase of local tumor control as com pared with conventional ERT alone or conventional ERT combined with an interstitial implant was observed, with an acceptable number of (late) normal tissue complications [3,7,18,[22][23][24]. However, due to variations in dose distribution, tumor size and irradiated volume, a straightforward comparison of LDR brachytherapy and conventional ERT is not possible.…”
Section: Clinical Reference Doses O F Ldr Brachytherapy In Head and Nmentioning
confidence: 99%
“…If LDR brachytherapy is used as a single modality in treating cancer of the oral cavity, the recommended dose is 65-70 Gy prescribed at a reference dose rate between 30-50 cGy/h [23,271, with as a consequence an overall treatment time limited to about 1 week, For such schedules an increase of local tumor control as com pared with conventional ERT alone or conventional ERT combined with an interstitial implant was observed, with an acceptable number of (late) normal tissue complications [3,7,18,[22][23][24]. However, due to variations in dose distribution, tumor size and irradiated volume, a straightforward comparison of LDR brachytherapy and conventional ERT is not possible.…”
Section: Clinical Reference Doses O F Ldr Brachytherapy In Head and Nmentioning
confidence: 99%
“…12 reported better local control in a group of patients who were treated with combination therapy with external radiation of< 40 Gy (92%) than in the group treated with combination therapy with external radiation of _> 40 Gy (64%). Fu et al 8 and Mendenhall et al) 1 also reported similar findings. These findings seem to be reasonable because the doses delivered with external irradiation at the primary tumor site were closely connected with tumor volume.…”
Section: Discussionmentioning
confidence: 56%
“…the small fraction of patients that would potentially benefit from elective neck dissection does not justify the procedure in the large number of TxNo patients that would receive no benefit. Fu, et al, 4 also report that neck recurrence can be controlled with a radical neck dissection in 80% of patients in whom the primary is controlled b~ the initial treatment. This control rate does not mclude one-third of their patients with neck metastases developing after treatment .of the primary lesion who were given no further therapy, and no patient was controlled when a combined resection was required for a recurrent primary.…”
Section: Discussionmentioning
confidence: 97%